PENGARUH PROMOSI DAN HARGA JUAL MOBIL TOYOTA TERHADAP KEPUASAN KONSUMEN PADA PT AUTO 2000 TANJUNG API-API PALEMBANG - Moh. Riduan; Umi Hasanah (JURNAL KOMPETITIF, 2020)
The background of this research is the satisfaction of consumers who are the priority in the Toyota automobile sales business as well as encouraged by the increasingly stringent level of competition and also given the number of competing companies of similar competitors. Promosion and selling price are some very important aspects because consumers want the maximum sastisfaction given company PT AUTO 2000 Tanjung Api-Api Palembang Based on the test result F, Fcount 21,052 > Ftable 2,40 and F significant 0,000>(α) 0,1 obtained the conclusion H0 rejected and independent simultaneously have a significant  effect  on  the  dependent  variables.  Then  t  test  result  on  variable promotion, tcount 4,503 > ttable 1,672 and t significant  0,000 < (α) 0,1 obtained conclusions H0 rejected and variable promotion partially significant effect on consumer satisfaction at PT AUTO 2000 Tanjung Api-Api Palembang. Last target of the test result on variable selling price tcount 1,917 > ttable 1,672 and t significant 0,060 < (α) 0,1. then in the conclusion of H0 rejected and the variable selling price in a partial has significant effect on consumer satisfaction at PT AUTO 2000 Tanjung Api-Api Palembang.While the calculation of R value of 65,2 % indicates that the relationship between independent variable promotion and the selling price of dependent variable consumer satisfaction  has a relationship that is relatively strong because it is at intervals > 0,25 – 0,75. Based on coefficient of determination indicating that the influence of promotion and selling price consumer satisfaction of 40,5 % and the remaining (100% - 40,5 %) = 59,5 % is influenced by other factors not included in this research. Keywords : Promotion, Selling Price, And Customer Satisfaction